2013
DOI: 10.17816/2074-0530-68371
|View full text |Cite
|
Sign up to set email alerts
|

Self-exciting oscillations in clutches of automobiles and tractors

Abstract: The authors present the experimental results proving that in the real exploitation of a vehicle or a tractor self-exciting oscillations do not occur in friction pairs of friction clutch. This refers to friction clutches with asbestos, asbestos-free polymer and sintered powder friction pads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A review of the design of the running systems of wheeled tractors showed that their adaptation to the row spacing is carried out by changing the gauge of the tractor wheels [15], which is achieved in various ways [16,17] carried out by devices of various designs [18,19]. Methods for changing the gauge of tractor wheels can be conditionally divided into two groups: changing the gauge by manual and mechanized methods.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the design of the running systems of wheeled tractors showed that their adaptation to the row spacing is carried out by changing the gauge of the tractor wheels [15], which is achieved in various ways [16,17] carried out by devices of various designs [18,19]. Methods for changing the gauge of tractor wheels can be conditionally divided into two groups: changing the gauge by manual and mechanized methods.…”
Section: Methodsmentioning
confidence: 99%